A Note on Fermi Walker Derivative with Constant Energy for Tangent Indicatrix of Slant Helix in the Lie Groups - Körpınar, Talat (AMER SCIENTIFIC PUBLISHERS, 2018)
In this manuscript, we present concept of new energy with Fermi-Walker (FW) derivative of tangent spherical image by using FW parallelism in Lie goups. By way of innovative illustration, we obtain FW parallelism condition for some vector fields. Furthermore, we obtain new characterization by some equations. Finally, we have new energy construction of frame of tangent spherical image in Lie goups.
Keywords: Energy; Slant Helix; Lie Groups; FW Derivative